How the forebrain transitions to adulthood: developmental plasticity markers in a long-lived rodent reveal region diversity and the uniqueness of adolescence - Garduño, B. Maximiliano; Hanni, Patrick; Hays, Chelsea; Cogram, Patricia; Insel, Nathan; Xu, Xiangmin (Frontiers in Neuroscience, 2024)
Maturation of the forebrain involves transitions from higher to lower levels of synaptic plasticity. The timecourse of these changes likely differs between regions, with the stabilization of some networks scaffolding the development of others. To gain better insight into neuroplasticity changes associated with maturation to adulthood, we examined the distribution of two molecular markers for developmental plasticity. We conducted the examination on male and female degus (Octodon degus), a rodent species with a relatively long developmental timecourse that offers a promising model for studying both development and age-related neuropathology. Immunofluorescent staining was used to measure perineuronal nets (PNNs), an extracellular matrix structure that emerges during the closure of critical plasticity periods, as well as microglia, resident immune cells that play a crucial role in synapse remodeling during development. PNNs (putatively restricting plasticity) were found to be higher in non-juvenile (>3 month) degus, while levels of microglia (putatively mediating plasticity) decreased across ages more gradually, and with varying timecourses between regions. Degus also showed notable variation in PNN levels between cortical layers and hippocampal subdivisions that have not been previously reported in other species. These results offer a glimpse into neuroplasticity changes occurring during degu maturation and highlight adolescence as a unique phase of neuroplasticity, in which PNNs have been established but microglia remain relatively high.